Analysis of the Impact of Financial Services Authority Regulations on the Development of the Financial Industry in Indonesia - Poernomo, Harry; Prasadjaningsih, Mc oetami (Universitas Islam Sultan Agung, 2024)
This research aims to analyze the impact of Financial Services Authority (OJK) regulations on the growth of the banking sector and the improvement of financial literacy and inclusion in Indonesia. The research was conducted using a qualitative method and a normative approach. Data were obtained through literature studies of laws and regulations, literature, journals, and other relevant sources. The results showed that OJK regulations have a significant influence on banking growth, although the impact is not always positive. On the other hand, OJK's efforts to improve financial literacy and inclusion through various policies are considered to have not yet yielded optimal results. A balanced regulatory formulation, cross-sector policy coordination, and policy breakthroughs are needed so that the implementation of financial literacy and inclusion is more effective. This research is expected to provide input for regulators in formulating policies that support the growth of the Indonesian financial services sector.